Sagittal plane ankle kinetics are associated with dynamic hip range of motion and gait efficiency in women with hip osteoarthritis. Issue 3 (21st June 2022) - Huang, Chun‐Hao; Aydemir, Burcu; Foucher, Kharma C.
Abstract: Loss of sagittal plane hip range of motion (ROM) is a commonly reported walking gait impairment in people with hip osteoarthritis (OA). The purpose of this study was to evaluate whether sagittal plane hip ROM reduction and the resulting altered sagittal plane ankle kinetics during gait influence the energy cost of walking in people with hip OA. We evaluated 24 women with unilateral hip OA (60 ± 9.1 years; 29.4 ± 6.1 kg/m 2 ). Sagittal plane hip ROM and peak ankle dorsiflexion moment were assessed by instrumented gait analysis. We also used a portable metabolic system to measure the energy cost of walking. Pearson correlations and regression analyses were performed to test our hypotheses. We found that greater involved limb sagittal plane hip ROM was associated with a larger ankle peak dorsiflexion moment at push‐off during gait ( R = 0.50, p = 0.01). Greater involved limb peak ankle dorsiflexion moment at push‐off was associated with a lower oxygen consumption during gait ( R = −0.51, p = 0.01). Involved limb peak ankle dorsiflexion moment at push‐off predicted 26% of the variance in O2 cost. Statement of Clinical Significance: Sagittal plane hip ROM was associated with peak ankle dorsiflexion moment at push‐off during gait in women with hip OA. Moreover, peak ankle dorsiflexion moment at push‐off was associated with the energy cost of walking. Therefore, modifying sagittal plane hip ROM and peak ankle dorsiflexion moment could be a possible rehabilitation strategy to improve gait efficiency in women with hip OA.